Examining the comprising constituencies of citizen\'s Mental Image of Urban Places with emphasis on phenomenology and environmental psychology approaches Case study: 1th and 18th districts of Tehran - mohammad Taghi Razavian; Zhila Sajadi; Morteza Ghourchi; zohreh mohammadganji (تحقیقات کاربردی علوم جغرافیایی)
The present study in dealing with the problem of weakening the connection between human and place in todaychr('39')s cities, is trying to examine the theories derived from the approaches of phenomenology and environmental psychology. The research method in the present study is a descriptive-comparative survey based on a documentary study and a questionnaire ". According to the statement of the problem and the choice of two zones 1 and 18 as a case study, Tajrish in District 1 and Shahrak-e-Valiasr in District 18 of Tehran were selected as a case study based on situational sampling. According to the type of research (descriptive -survey), 100 residents of Tajrish and 120 residents of Shahrak-e-Valiasr were selected by simple random method. Dependent variable is "Residentschr('39') mental image of urban places" (twenty indicators derived from theories proposed in phenomenological and environmental psychology approaches) and independent variables are including respondent individual characteristics (age, gender, occupation, education, marital status,…) . The respondent and the mentioned factors, the strengths and weaknesses of the twenty indicators should be identified and strategies should be proposed to improve the constructive dimensions of the mental image in the case studies. Statistical analysis of the data obtained through the questionnaire indicated that Despite the significant difference between the satisfaction of the components of the mental image in these two neighborhoods, There is a correlation between the individual characteristics of the respondents and the satisfaction of the mentioned components in both